Analisis Konten Rokok di Situs Web Berbagi Video YouTube: User Engagement Analysis - Ramadona, Aditya; Mellen, Renie Cuyno; Najiyati, Ifa; Farahdilla, Zakiya Ammalia; Padmawati, Retna Siwi (LPPM Hang Tuah Pekanbaru, 2023)
Penetration of the internet and social media in Indonesia is increasing, with the most significant percentage of its users coming from the youth. The internet and social media can be a medium for promoting and selling products to youth. This study aimed to identify and describe videos potentially suggested when users enter the keyword